Early-life RSV infection modulates innate immune events, preferentially enhancing allergen-induced type 2 lung inflammation in females. - Lydia Labrie; Rojine C McVea; Rami Karkout; Haya Aldossary; Véronique Gaudreault; Brian J Ward; Elizabeth D Fixman (PLoS Pathogens)
Respiratory syncytial virus (RSV) causes millions of hospitalizations and thousands of deaths per year globally. Early-life RSV infection is also associated with the subsequent development of wheezing and asthma, which exhibits sex-related disparities in incidence, epidemiology, and morbidity. The mechanisms that underlie these sex-specific effects are not clear. We have developed a combined infection-allergy model in which 10-day old mice are infected with RSV and subsequently exposed to a common allergen, house dust mite (HDM). We show that early-life exposure to RSV enhanced allergic lung inflammation upon HDM exposure 10 days after viral infection. Early-life RSV infection increased levels of the innate cytokine, IL-33, in the lung 6h following HDM exposure. Accumulation of CD11cmed eosinophils and group 2 innate lymphoid cells was more prominent in the lungs of female mice exposed to both RSV and HDM. Moreover, the numbers of IL-13+ T cells (both CD4+ and CD8+) in the lung were significantly increased in mice exposed to both RSV infection and HDM, although the expression of ST2 (the cognate receptor for IL-33) was not linked to T cell cytokine production. Inflammatory responses were maintained when the interval between RSV infection and HDM exposure was extended to one month. Thus, our results show that early exposure to RSV increased numbers of innate cells as well as T cells in response to a common allergen, whether delivered within days or after several weeks of viral infection and that most responses were enhanced in female mice. Our work highlights sex-specific impact of early-life viral infection on the developing lung, and suggests possible mechanisms to explain the subsequent predisposition to enhanced allergic responses long after viral clearance.